The 40th Annual Conference on South Asia Archives - South Asia, Center for (My University, 2011)
Program book, paper abstracts, and other materials from the 40th Annual Conference on South Asia, which was been held in Madison in October 2011.
Keywords: Conference; Barfield; Urdu; Tibetan; Telugu; Tamil; Sinhala; Sindhi; Sanskrit; Pali; Punjabi; Pashto; Nepali; Marathi; Malayalam; Hindi; Gujarati; Bengali; Asia; Bhutan; Tibet; Afghanistan; Nepal; Sri Lanka; Bangladesh; Pakistan; India; South Asia